Price Behaviour and Market Integration: Preliminary Evidence from the Ukrainian and European Union Rapeseed Markets - Mariusz Hamulczuk; Oksana Makarchuk; Edgardo Sica (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
This paper aims to provide preliminary evidence about the existence of horizontal integration between the rapeseed markets in Ukraine (UA) and the European Union (EU). To this end, both a trade analysis and a price analysis were carried out. In particular, the trade analysis was performed using yearly trade flows between the UA and EU, whereas price co-movement was assessed by means of linear vector error correction model (VECM) applied to weekly prices for rapeseed from 2008 to 2018. Our findings provide evidence of strong integration between the UA and EU markets in terms of the trade of rapeseeds, rape cake, and rape oil, as well as high horizontal rapeseed price transmission between the two economies.